HUBUNGAN STATUS GIZI DAN INDEKS GLIKEMIK PANGAN DENGAN KADAR GLUKOSA DARAH PASIEN DIABETES MELITUS TIPE 2 DI UPTD RSUD dr. H. BOB BAZAR, SKM TAHUN 2021 - Sukri, Achmad Doni Setiawan Sukri (Journal Aisyah University, 2022)
Diabetes mellitus is a disease of glucose metabolism disorders in which the body fails or is not good at controlling the glucose that enters from food so that blood glucose levels are high. The prevalence of diabetes mellitus in Lampung province based on doctor's diagnosis increased from 0.8% in 2013 to 0.99% in 2018. Type 2 Diabetes mellitus patients who were hospitalized at UPTD dr. H. Bob Bazar, SKM South Lampung in 2020 ranks first of the 10 most diseases with a total of 552 patients. The purpose of this study was to determine the relationship between nutritional status and food glycemic index with blood glucose levels in type 2 diabetes mellitus patients at UPTD RSUD dr. H. Bob Bazar, SKM 2021. This study uses a Cross Sectional approach with a sample of 40 people. The test used is the Pearson correlation test. Based on the results of the study, it is known that the distribution of the characteristics of respondents with the most gender is female (62.5%), the age of the most respondents is 46-55 years (45%). The results of the univariate analysis showed that the average blood glucose level (GDS) of 40 respondents was 240.58 mg/dl, the average Body Mass Index (BMI) of 40 respondents was 22.98 kg/m2 and the average glycemic index of food was 40. respondents was 53.56. The results of the bivariate analysis showed that there was a relationship between nutritional status and blood glucose levels with p-value = 0.001, there was no significant relationship between food glycemic index and blood glucose levels with p-value = 0.301. Keywords: Food Glycemic Index1, Diabetes Mellitus2, Blood Glucose Level3.